PS-068 Analysis and improvement of prescription and administration in hospital transitions. (25th February 2017) - Vilarrasa, L Canadell; Broseta, PA López; Parada, L Sánchez; Marqués, M Martín; López, A de Dios; Sirgo, G; Rodriguez, A; Esteban, F; Olona, M; Bodí, M
Abstract : Background: Anticholinergic drugs (AchD) are often prescribed in elderly patients. They may increase cognitive and functional disorders, decrease the effects of anticholinesterase drugs (AcsD) and cause other adverse reactions, especially in Alzheimer's disease (AD). Purpose: To analyse atropinic burden (AB) using various scales in order to quantify the associated risk and to identify the most prescribed AchD in hospitalised patients with AD. Material and methods: Bibliographic search in Pubmed using as the main terms 'atropinic', 'anticholinergic' and 'Alzheimer'. This was a retrospective study performed from May 2015 to July 2016. APD prescription software and DIRAYA database were used to obtain prescription, demographic and patient data. 9 scales (7 of them validated) were chosen to identify drugs with AB and to quantify them. Results: 49 hospitalised patients were studied, 26 men and 23 women, with an average age of 81.82±7.13 years. There were 6 deaths during hospitalisation (12.25%). All patients were receiving 1 or more AcsD to treat AD. 4 patients (8%) were not receiving AchD during hospitalisation while the rest were taking 1 or more AchD: 16 patients 1 drug (32.65%), 19 patients 2 drugs (38.77%), 5 patients 3 drugs (10.20%) and 3 patients were taking 4 AchD (6.12%). Only 1 patient was not at risk, 4 were at intermediate–low risk and 44 were at high risk according at least to 1 scale (89.79%). 28 patients were at high risk in 5 or more scales (57.14%). Psychotropic drugs with anticholinergic effects were prescribed in 28 patient (57%). Most prescribed drugs were haloperidol (11 patients, 22.45%), quetiapine (14 patients, 28.57%) and ipratropium (7 patients, 14.28%). Conclusion: It is common practice to prescribe AchD in elderly hospitalised patients with AD. Cumulative administration of these drugs makes this fragile type of patients especially vulnerable to anticholinergic adverse effects. References and/or acknowledgements: Villalba-Moreno AM, et al. Systematic review on the use of anticholinergic scales in poly pathological patients. Arch Gerontol Geriatr2015;62:1–8. Montrastuc F, et al . Atropinic burden of prescriptions forms in patients with Alzheimer disease: a cross-sectional study in a French pharmacovigilance database. EJC Pharmacology 2015;71 ./:891–5. Grey SL, et al . Cumulative use of strong anticholinergic medications and incident dementia. JAMA Intern Med 2015;175 :401–7. No conflict of interest